An 'incredible community' or 'disgusting' and 'weird'? Representations of breastmilk sharing in worldwide news media - Sally Dowling; Aimee Grant (Wiley, 2021)
Abstract Breastmilk sharing via the internet has become more popular in recent years, with a resultant increase in media attention. It is actively discouraged by public health bodies in at least three countries. We undertook a qualitative analysis of worldwide English language news media (online newspaper articles and transcripts of television and radio pieces) focusing on peer‐to‐peer breastmilk sharing during a 24‐month period (2015-2016). One hundred eleven news articles were analysed semiotically for positive (n = 49) and negative (n = 90) depictions of breastmilk sharing and the actors involved. Three countries published the majority of the articles: United States (n = 42), United Kingdom (n = 24) and Australia (n = 20). Topics associated with using shared breastmilk included perceived insufficiency, having surgery or taking medication, or the prematurity of the baby. Reports of women who gave and received breastmilk were largely positive although sometimes confused with women who sell breastmilk, who were demonised. The breastmilk itself, however, was considered as potentially contaminated and possibly dangerous; calls for action (n = 33) focused on increasing regulation and safety. Peer‐to‐peer milk sharing and the commercial availability of human milk are activities that occur within social and cultural contexts, and, as such, the ways in which they are represented in the news media reflect the ways in which they are also represented more widely in society. Increased understanding of normal infant feeding practices is needed, alongside guidance on how to better support breastfeeding. News media outlets can facilitate this through reporting risk in line with evidence. Further research should be undertaken to understand the safety of breastmilk sharing and the experience of those who participate.